Aberrant SIRT6 expression contributes to melanoma growth: Role of the autophagy paradox and IGF-AKT signaling. Issue 3 (4th March 2018) - Wang, Liwen; Guo, Weinan; Ma, Jinyuan; Dai, Wei; Liu, Lin; Guo, Sen; Chen, Jiaxi; Wang, Huina; Yang, Yuqi; Yi, Xiuli; Wang, Gang; Gao, Tianwen; et al.
ABSTRACT: Melanoma is among the most life-threatening cancers. The pathogenesis of melanoma has not been fully elucidated. Recently, dysregulated macroautophagy/autophagy has been found to play a critical but inconsistent role in modulating melanoma growth at different stages, with the regulatory mechanism unclear. The histone deacetylase SIRT6 (sirtuin 6) is a known autophagy regulator, and its involvement in cancer development has been reported. Therefore, we sought to determine the role of SIRT6 in melanoma growth and detect its possible link with autophagy in the current study. We initially observed that the expression of SIRT6 decreased in primary melanoma but increased in metastatic melanoma compared with melanocytic nevus. Notably, the expression of SIRT6 was significantly correlated with the expression of autophagy biomarkers including MAP1LC3/LC3 and SQSTM1/p62. Furthermore, SIRT6 suppressed the growth of primary melanoma but promoted metastatic melanoma development in an autophagy-dependent way in vitro . Moreover, SIRT6 exerted its regulation on melanoma growth via the IGF-AKT signaling pathway, and the intervention of AKT could partly reverse the effects of SIRT6 on melanoma growth by regulating autophagy. At last, we determined the effects of SIRT6 on melanoma development in vivo . Taken together, our findings demonstrate that the bimodal expression of SIRT6 at different melanoma stages plays a critical role in regulating melanoma growth through an autophagy-dependent manner, which indicates the potential of SIRT6 to be a biomarker and a therapeutic target in melanoma.